Unpacking the Mediating Role of Doctor–Patient Trust in the Service Quality–Loyalty Link: Insights from a Large Public Hospital in Shandong, China - Yu, Li Guang; Hoo, Wong Chee; Juan, Hu Li; Wolor, Christian Wiradendi (International Review of Management and Marketing, 2026)
Our research is done from the perspective of trust between doctors and patients. The study chose Shandong Provincial Hospital as the research object, trying to find out the relationship between the service quality of the hospital, patients’ trust in the hospital, and whether patients are willing to come to see a doctor again. The study used the knowledge of service encounter theory and service quality theory to design a questionnaire and send it to patients in the hospital to fill in. Then, we use a method called Structural Equality Modeling (SEM) to analyze the collected data.Results The study found that patients would trust the hospital more and be more satisfied with the hospital if the service quality of the hospital was good. Moreover, patients’ trust is like a bridge, which can connect good service with their willingness to come again. Specifically, whether the hospital’s medical equipment is good or not, whether the nurses are friendly or not, whether the doctors are skilled or not, and whether it is inconvenient to register and pay fees will all affect the patients’ overall satisfaction and whether they will come next time. In addition, the study also shows that patients generally trust doctors. This degree of trust is positively related to the quality of service, satisfaction and whether they are loyal. That is to say, the better the service, the more trust, satisfaction and willingness they have to come again. Therefore, we suggest that the hospital should constantly optimize the medical equipment and environment, make the medical team’s service awareness and professional ability stronger, improve those procedures, and open more channels for patients to give their opinions. By doing so, the quality of service will be improved all the time, and patients will be more willing to choose this hospital. Our research not only supplements the theory about the relationship between service quality and patient behavior in public hospitals in China, but also provides practical evidence for hospital managers to help them formulate patient-centered service improvement strategies.